Perancangan Keamanan Jaringan Metode Authentication Login Hotspot Menggunakan Router Mikrotik di PT. Nusindo Rekatama Semesta - Muhammad Fachry Altarik; Andriyan Dwi Putra (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
Nusindo Rekatama Semesta is a company located in the Sleman Regency area, Jombor Lor, Sinduadi. PT. Nusindo Semesta is a company in the corporate management industry that has been operating since February 2011. PT. Nusindo Rekatama Semesta provides wireless hotspot facilities where employees and visitors who come can take advantage of an internet connection that can be accessed via laptops, smartphones, or other devices such as those that support wireless technology. However, the implementation of hotspots needs to be corrected; for example, per-client bandwidth still needs to be focused. It aims to overcome per-client bandwidth usage and create a captive login portal as a security system so that those who do not have access rights cannot use internet access in the company. Using the hotspot login authentication system within the company. With the application of Mikrotik Router OS as a router in the company's network, it can overcome the instability of wireless network connections, and the captive portal login feature on Mikrotik can prevent users who do not have access rights from being able to use the internet access in the company.